The Effect Of Using Medial Arch Support On Dynamic Balance - Agus Setyo Nugroho; Prasetyo Catur Utomo (Jurnal Keterapian Fisik, 2022)
Background: Pes planus is a clinical orthopedic condition in which the medial longitudinal arch is not visible from birth and the area is covered with fatty tissue, by using medial arch support it is hope that it can encourage the formation of the medial longitudinal arch and position the sole of the foot in the correct potition The arch normally forms from the first 5 years with an age range of 2-6 years. The critical period for arch formation is 6 years of age (Campbell, 2012). In the early school years, 28% - 35% of children have pes planus deformities, 80% of whom are categorized as "moderate". This study aims to illustrate that the incidence of pes planus at the age of shildren requires early sedation because 80% of the pes planus in children is categorized as moderate . Methods: This research is a true experimental type with a ype of pre and post test design which aims to determine the effect of using medial arch support on the dynamic balance of pes planus students of MI Nurul Karim Colomadu. The subjects used were grade 1 - 5 students with the condition of pes planus who had determined the inclution and exclution criteria. The number of subjects was 29 people with male and female gender from a total population of 92 student Results: Using the Wolcoxon Correlation Test, it is known that the value of p = 0.000 (P <0.05) shows that there is an effect of the use of medial arc support on dynamic balance in flat foot patients. Conclution: The use of medial arch support has an effect on increasing dynamic balance in children with flat foot , so it is recommended to use medial arch support in children with flat foot.